Application Of Water Table Fluctuation Method To Quantify Spatial Groundwater Recharge Witidn The Southern Slope Of Merapi Volcano, Indonesia - Tjahyo Nugroho Adji (Indonesian Journal of Geography, 2007)
The southern slope of Merapi Volcano plays a significant role to Yogyakarta Municipality groundwater resources. Groundwater recharge, herein meant as the effective precipitation that infiltrates into unsaturated zone andpercolates to water table after exceeds the soi/field capacity, is the main subject in this article. The objective of this research is to apply WTF method to spatially define the groundwater annual recharge. Four wells are selected to represent some geomorphologic units. Then, four A WLR installed to record the yearly shallow groundwater table fluctuation. In addition, WTF method requires groundwaterfluctuation and specific yield data. The rate of groundwater recharge in every well confirms the varying value. However, it seems that geomorphologic unit may be principally control to the time series variation of shallow groundwater jluctuationthat results in groundwater recharge characteristic. The volcanic slope unit (above 600 m as!) has the lowest water table fluctuation indicates the resistant comportment to the annual rainfall. Ihis unit is characterized by the relatively high magnitude of recharge of approximately 4270 mm/year.